The effect of subjective age on loneliness in the old adults: The chain mediating role of resilience and self-esteem - Xie, Jin; Zhang, Bo; Yao, Zhendong; Zhang, Wenya; Wang, Jingli; Zhao, Chun-ni; Huang, Xinquan (Frontiers in Public Health, 2022)
Objectives This study aimed to explore the effect of subjective age on loneliness in old adults, and the mediating role of resilience and self-esteem in subjective age and loneliness. Methods Approximately 450 old adults from Jiangxi, Hunan, Henan provinces completed the third edition of the Loneliness Scale (UCLA-LS III), Age Decade Scale (ADS), Connor-Davidson Resilience Scale (CD-RISC), and Self-Esteem Scale (SES). Results (1) Subjective age was significantly positively correlated with loneliness. (2) Resilience, self-esteem, and loneliness were significantly negatively correlated. (3) Subjective age affected loneliness through the mediating effects of resilience and self-esteem, respectively. (4) Resilience and self-esteem played a chain mediating role between subjective age and loneliness. Conclusion Resilience and self-esteem can directly affect the loneliness of the old adults alone and can also affect the loneliness of the old adults through the chain mediating effect of resilience and self-esteem.